2017
DOI: 10.1021/acs.chemmater.7b03344
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Molecular Fluorophores in the Ammonothermal Synthesis of Carbon Dots

Abstract: Recently, molecular fluorophores were shown to be formed in the bottom-up chemical synthesis, contributing to the emission of carbon dots (CDs), derived from a citric acid precursor. We applied an ammonothermal synthesis toward CDs, employing two reactants citric acid and supercritical ammonia functioning as both solvent and precursor. The resulting nanoparticles are identified as amorphous aggregates of molecular fluorophores based on citrazinic acid derivatives, which resemble many of the emission features t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 56 publications
11
136
0
Order By: Relevance
“…In a number of brilliant studies, it was shown that, in C-dots formed by thermal treatment of citric acid + amine, the aromatic fluorophores and their associates are observed well before the carbonization occurs [18,[88][89][90][91]. Moreover, the fluorescent C-dots may totally consist of organic dyes [92][93][94]. As we seen below, these facts may suggest the principle of formation of ordered H-aggregated structures.…”
Section: Going Deeper Into Nanocarbon Structures and Their Formationmentioning
confidence: 80%
See 1 more Smart Citation
“…In a number of brilliant studies, it was shown that, in C-dots formed by thermal treatment of citric acid + amine, the aromatic fluorophores and their associates are observed well before the carbonization occurs [18,[88][89][90][91]. Moreover, the fluorescent C-dots may totally consist of organic dyes [92][93][94]. As we seen below, these facts may suggest the principle of formation of ordered H-aggregated structures.…”
Section: Going Deeper Into Nanocarbon Structures and Their Formationmentioning
confidence: 80%
“…Whereas the "molecular view" is dominant in the discussions of fluorescence mechanisms of carbon nanoparticles [18,93,144], suggesting molecular emitters located in the particle core [19], being extended to the surface [20] or forming the whole particle [94], there are spectroscopic properties that do not fit. In addition to the discussed above (Section 3.3) systematically observed very strong Stokes shifts, carbonic nanoparticles may possess the fluorescence lifetimes, τ F , that are unexpectedly much longer than that of typical organic dyes (e.g., fluorescein and rhodamines [261]).…”
Section: The Novel Excitonic Conceptmentioning
confidence: 99%
“…[49] Angewandte Chemie Zuschriften 5158 www.angewandte.de excitation wavelength-dependence is observed, leading to multi-color fluorescence under different excitation wavelengths.T herefore,their typical emission spectrum may arise not only from particles of different size but also from ad istribution of emissive domains and fluorophores on each dot. [57][58][59][60][61][62] All CNDs showed the typical wavelength-dependent emission in the blue region of the UV/Vis spectrum (Figure 2dand the Supporting Information, Figures S10 and S11).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…The emission is attributed to core and surface state related emission, in particular when excitation wavelength‐dependence is observed, leading to multi‐color fluorescence under different excitation wavelengths. Therefore, their typical emission spectrum may arise not only from particles of different size but also from a distribution of emissive domains and fluorophores on each dot . All CNDs showed the typical wavelength‐dependent emission in the blue region of the UV/Vis spectrum (Figure d and the Supporting Information, Figures S10 and S11).…”
Section: Figurementioning
confidence: 98%